Soundscape Semiotics Localization and Categorization - Glotin, Herve (IntechOpen, 2014)
Book Soundscape Semiotics - Localization and Categorization is a research publication that covers original research on developments within the Soundscape Semiotics field of study. The book is a collection of reviewed scholarly contributions written by different authors. Each scholarly contribution represents a chapter and each chapter is complete in itself but related to the major topics and objectives. The chapters included in the book are divided in two section. First section - Advanced Signal Processing Methodologies for Soundscape Analysis contains 5 chapters, and second section - Human Hearing Estimations and Cognitive Soundscape Analysis 3 chapters. The target audience comprises scholars and specialists in the field.